Training audio describers for art museums - Soler Gallego, Silvia; Luque Colmenero, María Olalla (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Audio description (AD) for art museums and exhibitions is a growing professional field. This article investigates the profiles of audio describers for art museums that exist today and presents a curriculum proposal for one of these profiles, namely the graduate in Translation Studies. This proposal consists of the incorporation of an internship in art museum AD into the Translation Studies curriculum. More specifically, this article describes the internship offered by the Kaleidoscope non-profit association, based in Granada, to graduates in Translation. Our proposal is discussed in relation to Kiraly’s (2000, 2012) social constructivist and holistic–experiential approaches to translator education and recent studies that advocate more internship opportunities for Translation graduates to help their meta-competence emerge (Kiraly & Hofmann, 2016) and to foster their employability (Schnell & Rodríguez, 2017).